Awareness and barriers to adoption of assistive technologies among visually impaired people in Nigeria. Issue 4 (8th August 2019) - Okonji, Patrick Emeka; Ogwezzy, Darlinton Chukwunalu
ABSTRACT: Assistive technology (AT), broadly defined as specialist equipment designed to promote computer access for people with disabilities, is increasingly becoming popular among people with vision impairment as computer use becomes commonplace in society. In developing and emerging economies, however, the adoption of ATs continues to lag behind the developed countries. This study explored barriers to adoption of assistive technologies among visually impaired people in five southern states in Nigeria. A mixed-method approach that employed qualitative interviews with 20 participants and structured questionnaires among 423 participants aged between 20 and 92 was employed. Participants were categorized into two groups: Visually Impaired Adults (VIAs, age range: 20–59 years) and Visually Impaired Older Adults (VIOAs, age range: 60 years and over). The findings show that while 36% of VIA had good awareness of the existence of ACTs, only 17.4% of them had good knowledge of usage. Among VIOA, 20% of them were aware of the existence of ACTs while only 8.07% had a good knowledge of how to use them. Implications of findings for interventions promoting barrier-free digital environment as well as strategies that could foster development of locally specific interventions for digital inclusion are discussed.